Resident-based learning model for sustainable resident participation in municipal solid waste management program - A. Ghazali; J. Tjakraatmadja; . Sunarti; E.Y.D. Pratiwi (Global Journal of Environmental Science and Management, 2021)
BACKGROUND AND OBJECTIVES: Encouraging resident participation in the Municipal Solid Waste Management system still becomes a challenge for cities in developing countries. Previous studies showed that existing education strategies ineffective and insufficient to change resident behavior sustainably. Therefore, this study aimed to develop a resident-based learning model to encourage sustainable resident participation in waste management programs at the household level using the Community of Practice approach.  METHODS: This study was a conceptual model study using a case study as the research strategy. The case being analyzed was Kawasan Bebas Sampah (Zero Waste Area) program implemented in Bandung City, Indonesia. The primary data was collected through field observation on the 8 Kawasan bebas sampah and in-depth interviews with 63 key informants comprising 31 key actors in the educational programs and 32 informants as resident representatives, conducted from January 2020 – November 2020. Additional data from the quantitative method was gathered in April 2021, focusing on surveying resident’s habits toward waste management as evidence of the program result. The respondents were 490 residents, chosen using the purposive-random sampling method.    FINDING: The findings showed that the education strategy implemented in Bandung City, Indonesia presented effective results, based on waste reduction rate reaching up to 0, 47% at the city level from 2019 to 2020. The survey provided evidence that the education program has succeeded in forming new habits for residents. Averagely 60% of respondents in each sample area have the habits and up to > 90% for the areas with more durable education program. Some critical points for education strategy implementations are identified. First, collaboration and supports from key stakeholders such as facilitators, local leaders, and educators become the enabler of the program. Second, key stakeholders need to identify knowledge and value needs before the program started. Third, the learning activities are conditioned to facilitate practice-based and dialogue-based learning through group and non-group learning activities. Fourth, local cadres are vital to sustaining the education program.  CONCLUSION: This study has succeeded in giving a new strategic approach to improve resident participation in municipal solid waste management. The resident-based learning model proposed in this study offered a more effective strategy for other cities in developing countries to improve the sustainable participation of residents in their waste management system. However, some adjustments may be required for residents with different characteristics. Future studies may focus on testing and refining the model to improve its applicability. ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================